Microstructural Characterization of Rapidly Solidified Laser Clad Layers Manufactured by Laser Processing of Inconel 617 - Moosa, Ahmed A.; Kadhim, Mohammed J.; Subhi, Akeel D. (Iraqi Journal of Laser, 2005)
The microstructures of rapidly solidified laser clad layers of laser cladding of Inconel 617 with different nickel-aluminum premixed clad powders are discussed. The effect of different cladding speeds on the microstructures of rapidly solidified laser clad layers is discussed too. The detailed microstructural results showed that different growth mechanisms are produced during rapid solidification. These are planar, cellular, cellular/dendritic and dendritic.